2019
DOI: 10.1016/j.jalz.2019.06.4950
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analysis of dementia and its clinical endophenotypes reveal novel loci associated with Alzheimer's disease and three causality networks: The GR@ACE project

Abstract: Introduction: Large variability among Alzheimer's disease (AD) cases might impact genetic discoveries and complicate dissection of underlying biological pathways. Methods: Genome Research at Fundacio ACE (GR@ACE) is a genome-wide study of dementia and its clinical endophenotypes, defined based on AD's clinical certainty and vascular burden. We assessed the impact of known AD loci across endophenotypes to generate loci categories. We incorporated gene coexpression data and conducted pathway analysis per categor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
88
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 50 publications
4
88
1
Order By: Relevance
“…Genome-wide association studies and their meta-analyses implicate more than 20 genetic loci, mainly involved in the immune system (directly or indirectly related to microglia), lipid metabolism, and endocytosis, as potential risk factors in sporadic late-onset Alzheimer's disease (Ridge et al, 2016;Jansen et al, 2019;Kunkle et al, 2019). However, clinic-pathological heterogeneity between AD cases complicate the understanding of the role these genetic components play in the manifestation of the disease (Moreno-Grau et al, 2019). It is suggested that genetic susceptibility may influence the effect of environmental and psychological factors on cognitive phenotypes during aging (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies and their meta-analyses implicate more than 20 genetic loci, mainly involved in the immune system (directly or indirectly related to microglia), lipid metabolism, and endocytosis, as potential risk factors in sporadic late-onset Alzheimer's disease (Ridge et al, 2016;Jansen et al, 2019;Kunkle et al, 2019). However, clinic-pathological heterogeneity between AD cases complicate the understanding of the role these genetic components play in the manifestation of the disease (Moreno-Grau et al, 2019). It is suggested that genetic susceptibility may influence the effect of environmental and psychological factors on cognitive phenotypes during aging (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The GR@ACE study 28 recruited AD patients from Fundació ACE, Institut Català de Neurociències Aplicades (Catalonia, Spain) and control individuals from three centres: Fundació ACE (Barcelona, Spain), Valme University Hospital (Seville, Spain) and the Spanish National DNA Bank Carlos III (University of Salamanca, Spain) (http://www.bancoadn.org). Additional cases and controls were obtained from dementia cohorts included in the Dementia Genetics Spanish Consortium (DEGESCO) 30 .…”
Section: Gr@acementioning
confidence: 99%
“…Genotyping was conducted using the Axiom 815K Spanish Biobank array (Thermo Fisher) at the Spanish National Centre for Genotyping (CeGEN, Santiago de Compostela, Spain) (Supplementary information, methods). We conducted previously described standard quality control prior to imputation 28 . In brief, individual quality control includes genotype call rates > 97%, sex checks and no excess heterozygosity; we removed population outliers as well (European cluster of 1000 Genomes).…”
Section: Gr@acementioning
confidence: 99%
See 2 more Smart Citations